2013
DOI: 10.1007/s00216-013-6781-9
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of needle trap micro-extraction and automatic alveolar sampling for point-of-care breath analysis

Abstract: Needle trap devices (NTDs) have shown many advantages such as improved detection limits, reduced sampling time and volume, improved stability, and reproducibility if compared with other techniques used in breath analysis such as solid-phase extraction and solid-phase micro-extraction. Effects of sampling flow (2-30 ml/min) and volume (10-100 ml) were investigated in dry gas standards containing hydrocarbons, aldehydes, and aromatic compounds and in humid breath samples. NTDs contained (single-bed) polymer pack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
78
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(78 citation statements)
references
References 25 publications
0
78
0
Order By: Relevance
“…Collection and processing of breath gas and room air samples An automated sampling device (PAS Technology Deutschland GmbH, Magdala, Ger many) combining mainstream capnometry and needle-trap microextraction (NTME) was used for breath gas sampling, as described previously (Trefz et al 2013b). In brief, this device enabled control of (i) sample volume and (ii) sampling conditions with respect to flow and pressure.…”
Section: Collection and Processing Of Faecal Samplesmentioning
confidence: 99%
See 2 more Smart Citations
“…Collection and processing of breath gas and room air samples An automated sampling device (PAS Technology Deutschland GmbH, Magdala, Ger many) combining mainstream capnometry and needle-trap microextraction (NTME) was used for breath gas sampling, as described previously (Trefz et al 2013b). In brief, this device enabled control of (i) sample volume and (ii) sampling conditions with respect to flow and pressure.…”
Section: Collection and Processing Of Faecal Samplesmentioning
confidence: 99%
“…VOCs desorbed from the NTDs were separated by a gas chromatograph (Agilent 7890 A) and detected by a mass selective detector (Agilent 5975 C inert XL MSD), as previously described in Trefz et al (2013b).…”
Section: Gc-ms Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Lab based Needle Trap Micro-Extraction Gas Chromatography Mass Spectrometry (NTME-GC-MS) at certain time points was applied to confirm marker identities. Details of analytical Brock et methods and instrumentation have been described before [9,10]. Briefly, breath gas for PTR analysis was continuously drawn from the alveolar tube in side stream mode (20 ml/min) by means of a t-piece.…”
Section: Methodsmentioning
confidence: 99%
“…35 Trefz et al investigated the sample flow rate and sample volume, along with the effect of humidity for breath analysis using a MA/EGDMA-packed needle and a triple-bed extraction needle. 49 They reported that the triple-bed extraction needle was not affected by the humidity. Determinations of VOCs in gaseous or breath samples by needle-type extraction devices are summarized in Table 1.…”
Section: Determination Of Vocs In Gaseous Samplesmentioning
confidence: 99%